2015
DOI: 10.1007/s11547-015-0511-7
|View full text |Cite
|
Sign up to set email alerts
|

High- and low-grade glioma differentiation: the role of percentage signal recovery evaluation in MR dynamic susceptibility contrast imaging

Abstract: The PSR evaluation proved better than CBV for determining the grade of brain and is therefore a useful tool to be considered in the MR evaluation of gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
0
15
1
Order By: Relevance
“…Additionally, authors used maximum CBV instead of median CBV and they did not perform post-hoc contrast agent leakage correction, which can lead to over or underestimation of true CBV. Since the percentage signal recovery (PSR) after bolus injection, a measure related to contrast extravasation, is known to be altered in different types of tumors [33], lack of correction for contrast agent extravasation alone may have altered their results. Similarly, Lev et al [21] observed a higher maximum rCBV in oligodendrogliomas compared with astrocytomas in a similar sized cohort of patients (N = 30; 8 oligodendrogliomas; 4 WHO II and 4 WHO III) even after leakage correction; however, the relatively low number of patients and use of maximum rCBV measurements likely biased their results toward more corticallybased lesions or tumors near vascular structures.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, authors used maximum CBV instead of median CBV and they did not perform post-hoc contrast agent leakage correction, which can lead to over or underestimation of true CBV. Since the percentage signal recovery (PSR) after bolus injection, a measure related to contrast extravasation, is known to be altered in different types of tumors [33], lack of correction for contrast agent extravasation alone may have altered their results. Similarly, Lev et al [21] observed a higher maximum rCBV in oligodendrogliomas compared with astrocytomas in a similar sized cohort of patients (N = 30; 8 oligodendrogliomas; 4 WHO II and 4 WHO III) even after leakage correction; however, the relatively low number of patients and use of maximum rCBV measurements likely biased their results toward more corticallybased lesions or tumors near vascular structures.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intracarotid injection of anti-tumor drug, cisplatin, demonstrated a 10-fold higher distribution in GBM area compared with the control normal brain tissue [21]. Increased tumor BBB disruption tends to correlate with higher-grade or more malignant glioma in human patients [22], and a systematic study in mice using real-time MRI indicated that the tumor BBB remains intact in earlier glioma stages but becomes significantly disrupted in the tumor core in late stages of glioma progression [23]. In part, this is a result of glioma malignancy grade being positively correlated with angiogenesis, leading to more immature and higher permeability vessels within the tumor [24,25].…”
Section: Leveraging Pathological Bbb Disruption In Gliomamentioning
confidence: 97%
“…To date, only two studies have investigated the utility of PSR for glioma grading, with both PSR to be significantly higher in LGG than in HGG. 35,36 Contrary to previous studies, Aprile et al. 35 did not find a significant difference in rCBV between the groups ( p > 0.05), despite having a larger sample size than some previous studies.…”
Section: Clinical Applications Of Psr and Rcbvmentioning
confidence: 57%
“…35,36 Contrary to previous studies, Aprile et al. 35 did not find a significant difference in rCBV between the groups ( p > 0.05), despite having a larger sample size than some previous studies. Interestingly, Smitha et al.…”
Section: Clinical Applications Of Psr and Rcbvmentioning
confidence: 57%